Estudio de compuestos orgánicos volátiles en la fabricación de suelas de poliuretano y su incidencia en la salud laboral de los trabajadores, y propuesta de un sistema de prevención de salud ocupacional en la empresa La Fortaleza CÍA. LTDA. - Barrionuevo Paredes, Milton Giovanny (2016)
This research studies the impact on health of workers of the company La Fortaleza Cia. Ltda., Causing volatile organic compounds (propylene oxide, and Toluene perchlorethylene) in the manufacture of polyurethane soles. a field study was conducted to determine the latent risks in each activity making soles (Injection, Washing and Painting), evaluate them and control them. Fieldwork was conducted with the application of Test total health-AMIEL Langner (TST) and sampling the gas meter MX6 iBrid. The lack of knowledge of workers about the risks and hazards involved, among other insolvencies; It requires comprehensive training of worker safety and environmental issues. Doses of volatile organic compounds in the manufacture of polyurethane soles cause serious diseases and thus the morbidity rate is high, the workspace is not optimal for what can happen highly significant disaster for workers. In accordance with purposing critical paradigm, reference was made to different methods and research techniques to develop an efficient study, applied to the 50 employees of the company's strength, achieving determine that the contamination levels of it are worrying so that the application of this study will help prevent involvement in workers' health through prevention system for the company occupational health Cia.Ltda La Fortaleza, whose design is the author's proposal